Evaluation use of bioaugmentation and biostimulation to improve degradation of sulfolane in artificial groundwater. (January 2021) - Chang, Shih-Hsien; Wu, Cheng-Fang; Yang, Chu-Fang; Lin, Chi-Wen
Abstract: Column systems were used to evaluate the effectiveness of different bioremediation methods (biostimulation (BS) and bioaugmentation (BA)) in treating sulfolane-contaminated groundwater. Batch test results confirmed that Cupriavidus sp. Y9 (Y9) was the most effective strain for BA. The optimal ratio of added native bacteria to Y9 was 10:3. The BA column adapted to a high sulfolane concentration (150 mg L −1 ) more rapidly and had higher sulfolane removal efficiency (90%) than did the BS column. The change in the biotoxicity of sulfolane-contaminated groundwater upon bioremediation, according to a Microtox test, revealed decreases in the inhibition of the passing of light by the BS column and BS + BA column of 38% and 63%, respectively. These results reveal that combining BS with BA can reduce the biotoxicity of sulfolane. The column tests confirmed the most effective added bacterium in BA, the operating conditions for high-efficiency bioremediation, and possible problems in its future application. The results provide an important reference for the design of methods for the remediation of contaminated sites. Graphical abstract: Image 1 Highlights: Biostimulation combined with biostimulation improved removal of sulfolane. Bioaugmentation effectively eliminated the biotoxicity of sulfolane. Specific bacterial seeding increased sulfolane removal efficiency. Mineralization of sulfolane was demonstrated by the formation of sulfate.